2013
DOI: 10.1007/s12105-013-0513-5
|View full text |Cite
|
Sign up to set email alerts
|

Primary Combined Neuroendocrine and Squamous Cell Carcinoma of the Maxillary Sinus: Report of a Case with Immunohistochemical and Molecular Characterization

Abstract: Neuroendocrine neoplasms represent a rare subset of tumors in the sinonasal tract. Combined tumors, with an endocrine and a non-neuroendocrine component, are exceedingly rare, and mainly consist of a combination of neuroendocrine carcinoma with adenocarcinomas. We present the clinico-pathologic and immunohistochemical features of a neuroendocrine carcinoma combined with squamous cell carcinoma, arising in the maxillary sinus. In addition, we evaluated the clonal origin of the two components through analysis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 17 publications
1
14
0
Order By: Relevance
“…Kao et al [24] also found p53 overexpression in 92% of their high-grade NECs whereas none of their WD-NEC or MD-NECs exhibited p53 increased expression. In a single case report of a combined NEC and SCC of the maxillary sinus, Frachi et al found a missense mutation of TP53 the NEC component but not in the SCC component [32]. In contrast, Halmos et al [29] found no p53 overexpression in a study of 10 laryngeal NECs.…”
Section: Molecular Pathologymentioning
confidence: 96%
See 1 more Smart Citation
“…Kao et al [24] also found p53 overexpression in 92% of their high-grade NECs whereas none of their WD-NEC or MD-NECs exhibited p53 increased expression. In a single case report of a combined NEC and SCC of the maxillary sinus, Frachi et al found a missense mutation of TP53 the NEC component but not in the SCC component [32]. In contrast, Halmos et al [29] found no p53 overexpression in a study of 10 laryngeal NECs.…”
Section: Molecular Pathologymentioning
confidence: 96%
“…The coexistence of neuroendocrine and non-neuroendocrine components in carcinomas of the head and neck is a known but rare phenomenon [32][33][34]. Whereas the WHO classifications of endocrine organs and GI system recommend that mixed neoplasms are those in which either component represent at least 30% of the tumor, no such recommendation exists for mixed neuroendocrine-nonneuroendocrine carcinomas of the head and neck.…”
Section: Mixed Neuroendocrine-nonneuroendocrine Neoplasms (Minens) Ofmentioning
confidence: 99%
“…Positivity for cytokeratins allows the distinction from other undifferentiated tumors, which may show neuroendocrine differentiation, including olfactory neuroblastoma and melanoma. Finally, sinonasal neuroendocrine carcinoma may occur in combination with squamous cell carcinoma or adenocarcinoma [20,21].…”
Section: Epithelial Neoplasmsmentioning
confidence: 99%
“…Staining of SCCs and BSCCs is strongly positive for 34βE12, while NECs are negative [6] [23]. p63 is also useful to identify basal and stem cells of the squamous epithelium and could be helpful to differentiate NECs from SCCs and BSCCs, as staining is positive for SCCs and BSCCs, but negative for NECs [6] [23]. In our case, tumor cells of the squamous cell differentiated area and a few basaloid nests were positive for 34βE12 and p63, but negative for the neuroendocrine markers.…”
Section: Discussionmentioning
confidence: 99%